SUSTENTABILIDADE NA ESCOLA UMA PROPOSTA PARA UMA EMEI DE SÃO PAULO, SP - Shahini, Cristina; Hernandez, Alberto; Buoro, Anarrita; Falcão, Fernanda (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
"Sustainability at school a proposal for an EMEI-SP is an experimental project that has been developed since 2013, aiming to implement integrated environmental practices focused on improving the school environment conditions and education for sustainability in a multi and interdisciplinary way. The project consisted of an evaluation of the building regarding thermal, acoustic and luminous comfort, and environmental awareness through lectures and workshops held with teachers, employees and school community. Various techniques and methodologies were used in addition to the use of art therapy and landscaping, among others, as a form of sensitization. Based on the building diagnosis, actions were proposed in the management of water, energy, waste and materials that involved both physical interventions and behavior change. Also, the school management was aligned for the implementation of pedagogical practices developed with children and actions developed by teachers and employees. These actions resulted in a goal initially aimed at this school: promoting the improvement of the quality of the school environment, awareness and education for sustainability, and the saving of public resources. The objective of this work was to produce a pilot project that provides subsidies for an Integrated Environmental Actions Program for Public Schools focusing on Sustainability.